Influence of Corporate Social Responsibility Actions on Customer Loyalty towards Nigerian Retail Banks within North Eastern Nigeria - Amsami, Maigana; Ibrahim, Siddiq Balal; Hamid, Abd Elsalam A (Asian Journal of Empirical Research, 2020)
The present study aims to test the relations between CSR and customer loyalty towards the retail banks in north eastern Nigeria. Cross sectional survey was conducted in 2019. Sample of 430 individual customers of the Nigerian retail banks within Bauchi, Maiduguri, Gombe, Jalingo, Yola, and Damaturu metropolitan towns in north eastern Nigeria participated in the survey as respondents. Hypotheses were tested using Path analysis, a component of structural equation modeling. Findings showed that CSR elements (legal, ethical, and philanthropic) positively influenced customer loyalty towards the Nigerian retail banks. The study concludes that involvement in CSR initiatives is essential actions that result in customer loyalty. It is thus recommended that CSR initiatives be practised by the Nigerian retail banks as a business strategy for creating competitive advantage and attracting lasting customer loyalty among customers.